Degradation of a dielectric barrier discharge plasma actuator - Andrew Ragai, Henry Rigit; Koon, Chun Lai; Bong, David B L (IEEE, 2009)
Dielectric barrier discharge is vulnerable to ion bombardment, radical species or ultraviolet radiations that can be emitted by plasma filaments in air under atmospheric pressure. In our experiments, traces of degradation on the actuator surface can be observed by naked eye after the discharge operation. The degradation could come from the non-uniformity of the electric field. Despite the degradation marks, some scratches due to the corona discharge process can be seen on the dielectric surface. The parametric study in this study reveals that the degradation on the actuator panel is subjected to a failure rate that increases with the cumulative time of plasma operation and the magnitude of supplied voltage. Besides, this study suggests that the severity of degradation can be lessened for a symmetric and larger gap design plasma actuator, since the concentration for the ion bombardment can be weakened at a particular discharge area.